Neotropical species of gripopterygid stoneflies (Plecoptera: Gripopterygidae) - Duarte Simoes, Tacio Vitor (2024)
The family Gripopterygidae occurs in the Austral Hemisphere and comprises about 330 species within 57 genera. About 110 species belonging to 28 genera are native to South America. Some are endemic to the Andean Region, while others reside in the Neotropical Region. In this latter region, Gripopterygidae has primarily been documented in the Brazilian Atlantic Forest, inland areas, and specific regions in northeastern Argentina, southern Paraguay, and Uruguay. Our research involved examining specimens from diverse Brazilian locations and compiling data sourced from the Plecoptera literature of the Neotropical Region. In this study, we present a comprehensive list of 62 Gripopterygidae species across four genera documented in Neotropical Region: 1) Gripopteryx Pictet, comprising 18 described species; 2) Guaranyperla Froehlich, comprising three species; 3) Paragripopteryx Enderlein, which includes 15 species, and 4) Tupiperla Froehlich, with 26 species. Additionally, we have morphologically characterized a specimen of Gripopteryx elisae Illies collected in Santa Catarina State, Brazil. We provide detailed information about the life stages associated with each species, documented records by administrative and natural areas, and information about the institutions housing the type series of Neotropical gripopterygids.